DEVELOPING LEARNING DOCUMENTS USING ASSURE DESIGN WITH PROBLEM-SOLVING STRATEGY ON SOCIAL ARITHMETIC MATERIALS TO INCREASE MATHEMATICAL PROBLEM-SOLVING ABILITY - Fitriani, Indah; Saragih, Sehatta; Murni, Atma (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2020)
This research is carried out due to students' low Mathematical Problem Solving Ability (Indonesian: KPMM) and the unavailability of learning documents that are following the demands of the 2013 Curriculum. This research produces learning documents using the ASSURE design with problem-solving strategies to improve students' KPMM. The development model used is the 4D model with validity instruments in the form of validation sheets of the syllabus, lesson plans (RPP), student activity sheets (LAS) and KPMM tests; practicality of the instruments in the form of student response questionnaires, teacher response questionnaires, and observation sheets; and effectiveness of the instruments in the form of KPMM test questions. The data were collected through questionnaires, observations and KPMM tests. The data were analyzed using validity analysis techniques; practicality analysis and effectiveness analysis. From the results of the data processing, the average score of the syllabus validation result is 3,56; RPP 3.60; LAS 3.51; and KPMM questions 3.55. The average scores of the student response questionnaire on limited trials and field trials are respectively 92.85% and 87.41% classified in the 'very practical' category. The average scores of the teacher response questionnaire and teacher observation are 96.54% and 94.31%. Based on the results of the effectiveness test, it can be stated that there are differences in KPMM students between the experimental class and the control class. It can be concluded that the learning documents developed have been valid, practical, and effective to improve students' KPMM.